Christmas Catastrophe : Geronimo Stilton #37 - Stilton, Geronimo (USA Scholastic Press, 2005)
Geronimo Stilton, adventuremouse? Not me! But surely a little skiing couldn't hurt a rodent, right? Wrong. Moldy mozzarella - when my ski trip landed me in the hospital, I was sure it was going to be the worst Christmas ever! But my family and friends had something else in mind....
Keywords: Mice -- Fiction; Christmas -- Fiction; Hospital -- Fiction; Skiiing -- Fiction